2019
DOI: 10.1093/applin/amz036
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Grammatical-Gender Marking in French as an Additional Language

Abstract: This investigation responds to the need for longitudinal data-driven research on additional-language (AL) acquisition by examining grammatical-gender marking among AL learners of French during a 21-month period, which included an academic year abroad (LANGSNAP corpus). The analysis of oral production consists of a generalized linear mixed model that examines a range of linguistic and extralinguistic factors shown to be important for gender marking in previous research, as well as a random effect for participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Despite the recent plethora of research on study abroad, students' morphosyntactic development, especially the development of their grammatical accuracy, is still understudied, and when it is investigated, the results usually contradict each other (Issa et al, 2020). The results of the analyses of the data in the spoken Chinese L2 corpus in this study lend support to the findings in the literature that students made progress in their grammatical accuracy in the spoken language after study abroad (e.g., Edmonds et al, 2020; Howard, 2005; Isabelli & Nishida, 2005). Specifically, at the end of study abroad, the error rate (including underuse) in the students' production of the Chinese perfective aspect marker le —which has been proven notoriously difficult for L2 learners to acquire—was significantly lower than that before the program, and at the same time, the overuse of le also decreased, suggesting overall more accurate use of the marker, closer to the target norm.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Despite the recent plethora of research on study abroad, students' morphosyntactic development, especially the development of their grammatical accuracy, is still understudied, and when it is investigated, the results usually contradict each other (Issa et al, 2020). The results of the analyses of the data in the spoken Chinese L2 corpus in this study lend support to the findings in the literature that students made progress in their grammatical accuracy in the spoken language after study abroad (e.g., Edmonds et al, 2020; Howard, 2005; Isabelli & Nishida, 2005). Specifically, at the end of study abroad, the error rate (including underuse) in the students' production of the Chinese perfective aspect marker le —which has been proven notoriously difficult for L2 learners to acquire—was significantly lower than that before the program, and at the same time, the overuse of le also decreased, suggesting overall more accurate use of the marker, closer to the target norm.…”
Section: Discussionsupporting
confidence: 86%
“…The design of this study is longitudinal in nature, in response to recent calls in the SLA field to conduct more longitudinal studies (e.g., Edmonds et al, 2020; Ortega & Byrnes, 2008; Ortega & Iberri‐Shea, 2005) and data‐driven research, especially on learner corpora (e.g., Hasko, 2013; McEnery et al, 2019). The same 62 students' data were examined once right before or at the beginning of their program in China, and once after or at the end of their program in China, after one semester or 1 year of study in China.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, regarding the gender feature, in contrast to its early mastery in L1 French, many L2 studies have shown persistent difficulties, particularly when the learners' L1 lacks grammatical gender (Carroll, 1989(Carroll, , 1999Guillelmon & Grosjean, 2001;Hawkins & Franceschina, 2004;Meisel, 2018;Surridge & Lessard, 1984;Wust, 2010). Nevertheless, gender seems to be mastered in high proficiency levels, even when the L1 does not instantiate it (Ayoun, 2007;Bartning, 2000;Edmonds, Gudmestad & Metzger, 2019;Prévost, 2009;Shimanskaya & Slabakova, 2017). Most studies have indicated that the masculine gender is overused (Harley, 1979;Bartning, 2000;Dewaele & Véronique, 2001;Edmonds & Gudmestad, 2018;Edmonds et al, 2019) and that animacy, morphophonological cues as well as noun frequency affect learning (Dewaele, 2015;Edmonds et al, 2019;Hardison, 1992;Shimanskaya & Slabakova, 2017;Surridge & Lessard, 1984).…”
Section: Aspects Of Tigrinya Grammarmentioning
confidence: 99%
“…Nevertheless, gender seems to be mastered in high proficiency levels, even when the L1 does not instantiate it (Ayoun, 2007;Bartning, 2000;Edmonds, Gudmestad & Metzger, 2019;Prévost, 2009;Shimanskaya & Slabakova, 2017). Most studies have indicated that the masculine gender is overused (Harley, 1979;Bartning, 2000;Dewaele & Véronique, 2001;Edmonds & Gudmestad, 2018;Edmonds et al, 2019) and that animacy, morphophonological cues as well as noun frequency affect learning (Dewaele, 2015;Edmonds et al, 2019;Hardison, 1992;Shimanskaya & Slabakova, 2017;Surridge & Lessard, 1984).…”
Section: Aspects Of Tigrinya Grammarmentioning
confidence: 99%